2012
DOI: 10.1039/c2jm33763k
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of high-quality CuInZnxS2+x core/shell nanocrystals and their application for detection of C-reactive protein

Abstract: Highly photoluminescent (PL) CuInZn x S 1+x nanocrystals (NCs) and CuInZn x S 1+x /ZnS core/shell NCs were successfully synthesized by a facile colloidal method. First, a facile and reliable non-injection method for the synthesis of photoluminescent CuInZn x S 2+x NCs was developed with inexpensive reagents. The relative PL quantum yields (QYs) of CuInZn x S 2+x NCs could reach up to 30%, with tunable emissions in the range 580-780 nm. Then, CuInZn x S 2+x /ZnS core/shell NCs were synthesized and showed greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…Therefore, QDs have been successfully utilized for rapid diagnosis. Specifically, QD immune-labeling, which is highly sensitive, quantitative, and reproducible technology that features a wide linear detecting range, has been developed to detect pathogens, characteristic proteins and even nucleic acids Liu et al 2013;Sapountzi et al 2015;Shen et al 2011b;Shen et al 2012;Zhou et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, QDs have been successfully utilized for rapid diagnosis. Specifically, QD immune-labeling, which is highly sensitive, quantitative, and reproducible technology that features a wide linear detecting range, has been developed to detect pathogens, characteristic proteins and even nucleic acids Liu et al 2013;Sapountzi et al 2015;Shen et al 2011b;Shen et al 2012;Zhou et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism of hydrophilic carboxylfunctionalized CdSe/ ZnS QDs has been previously described in the literature [24,25]. The dynamic light scattering analysis in Figure 2 shows that the average hydrodynamic size of carboxylfunctionalized CdSe/ Zn SQDs was 42.86 nm with Stdev 18.72 nm, and this size increased to 109.5 nm with Stdev 52.16 nm after dihydrazide modified and conjugation with antibodies, which indicated that antibodies were successful conjugated.…”
Section: Conjugation Of Antibodies To Qds Via Oxidized Fccarbohydratementioning
confidence: 75%
“…4(b), with In 3d 5/2 and In 3d 1/2 at 445 eV and 452.6 eV respectively. The In 3d peaks show a spin-orbit splitting of 7.6 eV which, from previous reports, 56,57 is indicative of In(III). The Zn 2p spectrum is shown in Fig.…”
Section: Spectroscopy Of Inp/zns Ncsmentioning
confidence: 88%